THE RELATIONSHIP BETWEEN PERCEIVED SOCIAL SUPPORT AND PSYCHOLOGICAL FACTORS RELATED TO RETURNING TO SPORT IN ADOLESCENTS FOLLOWING ANTERIOR CRUCIATE LIGAMENT RECONSTRUCTION. Issue 3 (31st March 2019) - Armento, Aubrey; Albright, Jay; Skelton, Anne; Gagliardi, Alexia G.; Howell, David R.; Daoud, Ariel Kiyomi; Mayer, Stephanie W.
Objectives: "Return-to-sport" (RTS) criteria following anterior cruciate ligament (ACL) reconstruction lacks standardization. In addition to functional strength and knee joint stability, psychological factors may also affect readiness to RTS. The present study aimed to assess the association between perceived levels of social support and confidence in RTS among adolescent athletes prior to undergoing ACL reconstruction. We hypothesized that athletes who perceived higher levels of social support would have greater confidence in their ultimate ability to return to their previous level of play after ACL reconstruction. Methods: Fifty-three subjects completed two questionnaires prior to undergoing ACL reconstruction: the Multidimensional Scale of Perceived Social Support (MSPSS) and a psycho-vitality (PV) questionnaire. We performed a multiple linear regression to assess if MSPSS score was associated with confidence in returning to sport (PV score), while controlling for the independent effects of age and gender. Independent sample t-tests were also used to compare MSPSS scores between those who did and did not state that they had doubts in their ability to RTS and those who were and were not willing to settle for a less strenuous sporting activity than previously, based on the PV questionnaire responses. Results: The mean age of participants was 15.6±1.7 years (range 9-18 years) with 42% males. There was no significant association between MSPSS total score (mean= 6.22±0375, range= 4-7) and PV total score (mean= 13.8±3.0, range= 8-18; ß coefficient= -0.63, 95% CI= -1.77, 0.52, p = 0.28). Those who reported doubts in returning to sport did not significantly differ than those who reported no doubts (n=19) in MSPSS total score (6.07±0.82 vs. 6.30±0.70; p = 0.29; Cohen's d= 0.31). Similarly, those who did and did not respond that they were willing to settle for a less strenuous sporting activity had similar MSPSS scores (6.14±0.81 vs. 6.47±0.45; p= 0.17; Cohen's d= 0.44). Conclusion: Previous studies suggest that psychological factors play a role in successful RTS, yet the specifics of how this pertains to adolescent athletes remain unknown. The present study suggests that prior to ACL reconstruction, perceived social support does not significantly influence confidence in the ability to ultimately RTS following surgery and subsequent rehabilitation in young athletes. Future studies will aim to correlate these variables between pre-operative and actual RTS time points, as well as to investigate how other factors, such as motivation and self-esteem, are influenced by social support and affect ultimate RTS success.